Permainan Estafet Kelereng uUntuk Meningkatkan Spirit Ta’awun Anak Usia Dini - Amanullah, Akhmad Syah Roni; Syarifah, Siti Nur (Proceedings of Annual Conference for Muslim Scholars, 2024)
This research was conducted at MUSLIMAT NU 03 PAMBON Kindergarten, Brondong District, Lamongan Regency, with children aged 4-5 years as the object of research. The purpose of this study was to determine the increase in the spirit of ta'awun for children aged 4-5 years in kindergarten MUSLIMAT NU 03 PAMBON. The method used in this research is experimental quantitative method with Pretest-Posttest Group design. The experimental group used marble relay game and the control group used rubber relay game. The results of the t-test obtained the average posttest value of the children who participated in the marbles relay game had a value of 82.17 and the average posttest value of the children with the rubber relay game was 69.92. Initially the children had a low level of spirit of ta'awun and after participating in the marbles relay game and the rubber relay game the spirit of ta'awun increased. In conclusion, the marbles relay game and the rubber relay game can increase children's spirit of ta'awun but the marbles relay game has a higher value than the rubber relay game.